Citrus Black Spot - Megan M. Dewdney; Natalia A. Peres (EDIS, 2018)
This 2-page fact sheet is a minor revision written by Megan M. Dewdney and Natalia A. Peres, and published by the Plant Pathology Department, July 2018.